2011
DOI: 10.2355/isijinternational.51.1383
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics and Mathematical Modeling of Hydrogen Reduction of NiO&ndash;WO<sub>3</sub> Precursors in Fluidized Bed Reactor

Abstract: In the present work, Fluidized bed reduction of NiO-WO3 precursors was investigated isothermally at temperatures 973-1 273 K. The reaction progress was monitored by analysis of H2O evolved during the reaction process using a gas chromatograph instrument. A theoretical model based on intrinsic chemical reaction rate constants and thermodynamic equilibria was developed to estimate the apparent reaction rate constant for the reduction reaction. In developing the model, the particles are considered to be in a comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 21 publications
(24 reference statements)
1
12
0
Order By: Relevance
“…They reported that using fluidized bed reactor operating at a lower temperature and just above the minimum fluidization velocity has been found to be acceptable in obtaining nano scale-sized particles of Fe 2 Mo. Ahmed et al [28] studied the kinetics of NiO-WO 3 precursors with hydrogen in a fluidized bed reactor operating at just above the minimum fluidization velocity. They suggested that the process conditions would have impact on the particle size of the product.…”
Section: Introductionmentioning
confidence: 97%
“…They reported that using fluidized bed reactor operating at a lower temperature and just above the minimum fluidization velocity has been found to be acceptable in obtaining nano scale-sized particles of Fe 2 Mo. Ahmed et al [28] studied the kinetics of NiO-WO 3 precursors with hydrogen in a fluidized bed reactor operating at just above the minimum fluidization velocity. They suggested that the process conditions would have impact on the particle size of the product.…”
Section: Introductionmentioning
confidence: 97%
“…Minimum fluidization velocity (U * m f ) at room temperature was firstly determined experimentally and corresponding U m f values at higher temperatures were calculated according to Equation (1). More details of the experimental setup can be found elsewhere [3]. The fluidized-bed reduction experiments were conducted isothermally.…”
Section: Methods (Techniques and Procedures)mentioning
confidence: 99%
“…However, XRD results of reacted NiO-WO 3 precursors revealed the presence of WO 2 phase in NiO-WO 3 precursor as a main phase formed at 1048 K together with W, Ni, WN 2 and WN. This phase resulted from the stepwise reduction of WO 3 . With further rise in temperature, the WO 2 phase is subsequently reduced to W metal, which is then reacted with N 2 gas to produce tungsten nitrides (WN and WN 2 ).…”
Section: Reduction-nitridation Of Ni-w-o Mixed Oxidesmentioning
confidence: 99%
See 2 more Smart Citations